Second Screening as Convergence in Brazil and the United States - McGregor, Shannon (2017)
Second screening is widespread worldwide, particularly in younger populations. We analyze a survey of college students in Brazil and the United States to compare second screening frequency, types, platforms, and motivations between the two countries. Despite lower Internet penetration, Brazilians second screen significantly more than Americans, a result of the country’s tradition of interacting with producers of television. In both countries, those who use the interactive affordances of social media are more likely to second screen. As such, we posit this unique audience-driven act works to bridge Web-connected devices and television to create a converged atmosphere.